Six Sigma in the Service Industry - Wu, Shuang; Tang, Hong (International Journal of Global Economics and Management, 2024)
This study sorts out the origin and development of Six Sigma management theory, elaborates on the connotation of Six Sigma and the current situation of industrial application, focuses on the application of Six Sigma in the service field, and analyzes and reviews the application of Six Sigma from the micro and practical levels. The final conclusion is that service industry companies improve service quality and efficiency by using Six Sigma methods, train employees to enhance their professional abilities, and optimize service processes under data-driven conditions to achieve financial efficiency enhancement.